MERAWAT KERUKUNAN UMAT BERAGAMA BERBASIS KEARIFAN LOKAL DI MANOKWARI PAPUA BARAT - Muhammad Sadli Mustafa (Al-Qalam, 2019)
This study aims to describe the general condition of religious harmony in Manokwari, reveal local wisdom that has a nuance of harmony found in the local community, and reveal the function of local wisdom in caring for inter-religious harmony. This research is a qualitative research. Data were collected by observation, interview and documentation techniques and analyzed qualitatively. The results showed that the condition of religious harmony in Manokwari was still maintained, despite certain frictions, but did not lead to conflicts between religious communities due to the synergy between government, customary and religious institutions that continued to engage in dialogue to reduce the potential for conflict. Nani akei sut dani, dani dekei sut nani, (you are good to me, I am good to you) is one of the local wisdoms of the indigenous Manokwari tribe that is full of nuances of religious harmony. Local wisdom is still carried out today until now in the social life of the local tribes of Manokwari and taught from generation to generation by each family from the existing tribes.